2010
DOI: 10.1136/ard.2009.123729
|View full text |Cite
|
Sign up to set email alerts
|

No overall progression and occasional repair of erosions despite persistent inflammation in adalimumab-treated rheumatoid arthritis patients: results from a longitudinal comparative MRI, ultrasonography, CT and radiography study

Abstract: AimTo monitor joint infl ammation and destruction in rheumatoid arthritis (RA) patients receiving adalimumab/ methotrexate combination therapy using MRI and ultrasonography. To assess the predictive value of MRI and ultrasonography for erosive progression on CT and compare MRI/ultrasonography/radiography for erosion detection/monitoring. Methods Fifty-two erosive biological-naive RA patients were followed with repeated MRI/ultrasonography/ radiography (0/6/12 months) and clinical/biochemical assessments during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 44 publications
6
97
2
2
Order By: Relevance
“…This might explain that the timeintegrated level of CRP was correlated with radiographic progression and IL-6 was not. Previous studies showing a correlation between cumulative levels of systemic inflammation and joint destruction assessed cumulative CRP burden as a proxy of joint inflammation (23,24,33). Interestingly, our data suggested that the impact of systemic inflammation on radiologic progression was independent from joint inflammation.…”
Section: Discussionsupporting
confidence: 58%
“…This might explain that the timeintegrated level of CRP was correlated with radiographic progression and IL-6 was not. Previous studies showing a correlation between cumulative levels of systemic inflammation and joint destruction assessed cumulative CRP burden as a proxy of joint inflammation (23,24,33). Interestingly, our data suggested that the impact of systemic inflammation on radiologic progression was independent from joint inflammation.…”
Section: Discussionsupporting
confidence: 58%
“…The selected papers were then divided among the group members and assessed according to an agreed scoring sheet (for results of Evaluation score, see Table 1) 4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]…”
Section: Resultsmentioning
confidence: 99%
“…A high level of agreement for detection of bone erosions in wrist and MCP joints in RA patients (concordance at 77-90% of sites) between MRI and computed tomography (CT), the gold standard reference for detection of bony Old transspinal fracture through syndesmophytes, vertebral disc, and posterior elements of the spine (solid arrows) with marked secondary degenerative changes destruction, documents that MRI erosions represent true bone damage [68][69][70][71].…”
Section: Mri In Rheumatoid Arthritismentioning
confidence: 99%